Tingkat Pengetahuan Nutrisi Olahraga Pada Personal Trainer Di Surabaya - Nufi Saidatus Tsaniyah; Anin Dita Safitri; Fina Luluk Chumaidah; Nurhadi; Thoriq Munir Alkatiri; Agus Hariyanto (Indonesian Journal of Kinanthropology (IJOK), 2026)
Background: Sports nutrition knowledge is an essential competency for personal trainers in supporting client health, safety, and fitness goal attainment. This study aimed to determine the level of sports nutrition knowledge among personal trainers and to identify the relationships among nutrition knowledge components. Methods: A descriptive quantitative approach with a cross-sectional design was applied. A total of 102 personal trainers in Surabaya were recruited using convenience sampling. Data were collected using the Abridged Nutrition for Sport Knowledge Questionnaire (A-NSKQ), which assesses general nutrition knowledge, sports nutrition knowledge, and supplement knowledge. Data were analyzed using descriptive statistics and inferential analysis with Spearman rank correlation tests Results: Most personal trainers demonstrated a low level of sports nutrition knowledge (69.6%), and total A-NSKQ scores were predominantly classified as low (60.8%). General nutrition knowledge was classified as moderate to good and was not accompanied by adequate sports nutrition knowledge. Correlation analysis revealed significant positive relationships between general nutrition knowledge, sports nutrition knowledge, and total A-NSKQ scores. Conclusions: The level of sports nutrition knowledge among personal trainers in Surabaya remains low. These findings indicate the need for competency development through evidence-based sports nutrition education and training to enable personal trainers to provide accurate, safe, and effective nutrition recommendations in support of client fitness goals.